Bem-estar e qualidade de vida na aposentadoria: percepção de servidores públicos da universidade federal da Paraíba - Lima, Maria do Socorro (2017)
This study aims to analyze the perceptions of public servants of the Center for Communication, Tourism and Arts (CCTA), from the Federal University of Paraíba (UFPB), on welfare and quality of life in retirement, as well as on changes in life postretirement. Therefore, the relationship between the retired people and the UFPB was identified through services that promote well being and quality of life and, moreover, the activities developed by the newly retired that promote quality of life and well-being. From the methodological point of view, this is a descriptive and exploratory research which aims to analyze the perceptions of a group of servers in the post-retirement phase, from the qualitative approach, using for the data collection an instrument containing an interview half structured. The sample consists of 08 (eight) retired employees in the last (04) four years and who performed their functions in administrative positions in the CCTA / UFPB. For the data processing, the technique of content analysis, proposed by Bardin, is used. According to the results, the data indicate that post-retirement life reveals more positive rather than negative perceptions. Also, is observed the consistency the with non-dissociation of the terms quality of life and well-being. The majority of the participants recognize in the retirement a gain of free time, involving flexibility of schedules for the family, the leisure, the practice of physical activities and health care. They also point out that they lack the work environment and socializing with their colleagues, as well as wage losses as negative factors after retirement. The coexistence of labor represents friendly ties with the institution. The public policies related to the retired server are pointed out as unfavorable, arbitrary and with no positive perspectives. Regarding the preparatory programs for retirement, most of interviewed people claim to be unaware of them. Therefore, it is important to promote actions, to plan adequately and widely disseminated concurrently with the work linkages of the server with the institution. Such suggestions will be taken to the Coordination of Quality of Life (CQV), linked to the Pro-Rector's Office of People Management (PROGEP / UFPB), in order to adopt practices that may generate new perspectives, not only in the performance of the work activities of the server as well as at the time of shutdown. We feed the perspective that the engaged server in such actions can perceive retirement not only as a reorganization of life, but also as a reconstruction in the way of thinking and seeing the future, in search of well-being and quality of life after the retirement.